2021
DOI: 10.1039/d1ra03734j
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the impact of strontium doping on the optical, electronic and electrical properties of nanostructured 2H-CuFeO2 delafossite thin films

Abstract: Facile synthesis of the challenging 2H-CuFeO2 delafossite nanostructured thin films is reported, and the effect of Sr doping is revealed experimentally and theoretically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…32 Although there are few reported Raman spectra of pure 2H-CuFeO 2 , doublet peaks (351 and 365-375 cm À1 ) are commonly observed in the E g mode region. 34,35 In the present study, distinct Raman peaks derived from 2H-CuFeO 2 were not observed throughout the experiments, suggesting that 2H-type was a minor product, as is common in other hydrothermal reactions. [11][12][13]36,37 The wide-scan XPS in Fig.…”
Section: Characterisation Of Cufeo 2 Films Hydrothermally Grown On Ft...mentioning
confidence: 40%
“…32 Although there are few reported Raman spectra of pure 2H-CuFeO 2 , doublet peaks (351 and 365-375 cm À1 ) are commonly observed in the E g mode region. 34,35 In the present study, distinct Raman peaks derived from 2H-CuFeO 2 were not observed throughout the experiments, suggesting that 2H-type was a minor product, as is common in other hydrothermal reactions. [11][12][13]36,37 The wide-scan XPS in Fig.…”
Section: Characterisation Of Cufeo 2 Films Hydrothermally Grown On Ft...mentioning
confidence: 40%
“…A few drops of hydrochloric acid (HCl) were added, and the mixtures were kept under vigorous magnetic stirring at 60 °C for 1 h, resulting in very clear solutions. The solutions were transferred to the deposition chamber equipped with the ultrasonic spray setup (SONAER-Ultrasonics) set at a frequency of 130 kHz and an applied power of 2.8 W. The selected substrates were the silicon wafer Si(100) with dimensions of 1–1.5 cm. The substrates were ultrasonically cleaned with distilled water, ethanol, and acetone consecutively for 15 min and finally dried in an air stream.…”
Section: Methodsmentioning
confidence: 99%
“…The extremely correlated 4f-related electronic states of Nd were modulated by the self-interaction correction (SIC) approach developed by Toyoda . The SIC approach is utilized to obtain a more realistic description of the disordered local moments of the material under investigation as indicated before. , For the parameterization of the exchanged energy, local density approximation (LDA) is employed in which SIC is included in the KKR-CPA–SIC–LDA package as implemented into MACHIKANEYAMA2002 . A total of 500 K-points in the whole first Brillouin zone were taken into account and the scalar relativistic approximation is incorporated as well.…”
Section: Methodsmentioning
confidence: 99%